1980
DOI: 10.1002/jlac.198019800414
|View full text |Cite
|
Sign up to set email alerts
|

Stoffwechselprodukte von Mikroorganismen, 189. Strukturaufklärung und Partialsynthese des Nucleosidantibiotikums Nikkomycin B

Abstract: Das Kulturfiltrat von Streptomyces tendae, aus dern die Nucleosidantibiotika Nikkomycin Z2) (la) und Nikkomycin X3) ( l b ) isoliert werden konnten, lieferte noch Nikkomycin B (7), das anstelle des 3-Hydroxypyridin-Systems von 1 einen p-Hydroxyphenyl-Rest im Aminosaurebaustein 6 enthalt. Dieser ist peptidartig mit einer 5-Aminohexuronsaure verkniipft, an die 4-Formyl-4-imidazolin-2-011 N-glykosidisch gebunden ist. Die Ableitung der Konstitution des neuen Aminosaurebausteins gelang durch Massenspektrometrie und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…[54] Double allylic alcohols are found as subunits of many natural products, for example, in metabolites with ionophoric activity isolated from marine sponges and microorganisms. [55] Starting from the dioxanone hydrazone (S)-37, a variety of a-substituted protected ketodiols 74 could be synthesized by the procedure described (90-94 % ee; Scheme 22). A racemization-free Wittig methylenation of these ketones gave the exocyclic olefins 75.…”
Section: Methodsmentioning
confidence: 99%
“…[54] Double allylic alcohols are found as subunits of many natural products, for example, in metabolites with ionophoric activity isolated from marine sponges and microorganisms. [55] Starting from the dioxanone hydrazone (S)-37, a variety of a-substituted protected ketodiols 74 could be synthesized by the procedure described (90-94 % ee; Scheme 22). A racemization-free Wittig methylenation of these ketones gave the exocyclic olefins 75.…”
Section: Methodsmentioning
confidence: 99%
“…The signals of the AA'BB' coupling system appeared at d 6.72 and S 7.06. The HMBCspectrum revealed that the chemical shifts of the carbon atoms 5-C and 8-C are chemical shift values typical for /?ara-substituted moieties of similar structures 9) Numbering of atoms see Figure 3.…”
Section: Isolation and Physicochemical Properties Of The Mutasynthetimentioning
confidence: 98%
“…2 were obtained when Amberlite fractions containing peaks on HPLC were pooled and again analysed by HPLC. It is known that wild-type produces several chemically related nikkomycins that have biological activity, with nikkomycin Z and X being the most abundant in culture broths [4,[13][14][15]. The nikkomycin Z and X peaks in wild-type (Fig.…”
Section: Analysis Of the Mutantsmentioning
confidence: 99%